A Molybdenum Carbide Nanotubes Modified Electrode as the Functionalized Sensing Platform for Electrochemical Detection of Dopamine. Issue 5 (12th February 2019) - Li, Ke; Han, Yanchao; Li, Jing; Xing, Huanhuan; Chen, Lei; Li, Guang; Zhu, Xiaoqing; Wang, Erkang
Abstract: In this work, molybdenum carbide (Mo2 C) nanotubes were prepared via the self‐degradable template method and high‐temperature calcination, and then were successfully used to modify glassy carbon electrode (CGE) for the high‐sensitivity determination of dopamine (DA) without the inference of ascorbic acid(AA) and uric acid (UA). The surface morphology of Mo2 C nanotubes has been investigated by scanning electron microscope (SEM) and transmission electron microscope (TEM). Owing to the enhanced electron transfer rate and high surface area of Mo2 C, the modified electrode not only exhibits very excellent electrochemical performance for DA, but also has good analytical performance for DA in the mixture with AA and UA through differential pulse voltammetry (DPV), which can be applied for DA detection with wide linear range(0.005–50 μmol L −1 ) and low detection limit 0.001 μmol L −1 . The modified electrode has been applied to detect DA in DA hydrochloride injection by using standard adding method with satisfactory results. Abstract :